IMPROVED SOLUBILITY OF CHOLECALCIFEROL AS BOVINE SERUM ALBUMIN (BSA) NANOPARTICLES - TANJUNG, YENNI PUSPITA; BARLIANA, MELISA INTAN; JONI, I. MADE; CHAERUNISAA, ANIS YOHANA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to report the optimum formula for BSA nanoparticles cholecalciferol (BSA-NP cholecalciferol), which can increase the solubility of cholecalciferol. Methods: BSA cholecalciferol nanoparticles was prepared by desolvation method with variations in solvent/non-solvent ratio, BSA concentration, pH of BSA solution, and cholecalciferol concentration. For this purpose, particle size, polydispersity index, and zeta potential were measured. Furthermore, the solubility test of the best BSA-NPs cholecalciferol formula was carried out. Results: The most optimal BSA nanoparticle cholecalciferol characterization results have a particle size of 166.6±50.3 nm, a zeta potential of-32.1 mV, and a percentage encapsulation efficiency (%EE) for cholecalciferol of 82.9±0.72%. The solubility of BSA-NP cholecalciferol is four times higher than that of pure cholecalciferol. Conclusion: The optimum formula for BSA-NP cholecalciferol with a solvent/non-solvent ratio of 1/2, a concentration of BSA of 2.5%, a BSA solution pH 6, and a cholecalciferol concentration of 0.1% will increase the solubility of cholecalciferol by four times compared to pure cholecalciferol.